A milk-derived pentapeptide reduces blood pressure in advanced hypertension in a CCK system-dependent manner. Issue 11 (16th October 2020) - Koyama, Daiki; Sasai, Masaki; Matsumura, Shigenobu; Inoue, Kazuo; Ohinata, Kousaku
Abstract : Orally administered KFWGK exhibits potent and long-lasting antihypertensive effects in SHR with advanced hypertension, at which known hypotensive drugs are sometimes less effective. The minimum effective dose of KFWGK was 5 μg kg −1 . Abstract : We recently found that a peptide that activates the cholecystokinin (CCK) system effectively reduces blood pressure in spontaneously hypertensive rats (SHR) after the development of hypertension, after which hypotensive drugs are sometimes less effective. In this study, we investigated the vasorelaxation and antihypertensive effects of a peptide derived from a milk protein in SHR with advanced hypertension. The vasorelaxing activity was measured using the mesenteric artery isolated from SHR and the systemic blood pressure was measured by the tail-cuff method. KFWGK was released from bovine serum albumin (BSA) and the model peptide after subtilisin digestion. KFWGK relaxed the mesenteric artery and this vasorelaxation activity was inhibited by lorglumide, an antagonist of the CCK1 receptor. KFWGK more potently relaxed the artery from advanced-stage SHR than that from early-stage SHR. Orally administered KFWGK exhibited potent and long-lasting antihypertensive effects in SHR after the development of hypertension (the minimum effective dose was 5 μg kg −1 ). The KFWGK-induced antihypertensive effects were also blocked by a CCK antagonist, suggesting that it activates the CCK system. In conclusion, KFWGK, a CCK-dependent vasorelaxant peptide, exhibited potent antihypertensive effects in SHR after the development of hypertension.